Food security, food safety, food quality : current developments and challenges in European Union law - Hartel,Ines,Ed (Forum Umwelt-, Agrar- und Klimaschutzrecht, 2016)
"Today security, quality and the availability of food are very important. The complex relations of the above mentioned issues evole in different fields of law. This book...covers a wide range of topics via analysis and discussion in the European context, such as the right to food, Common Agricultural Policy, contractual relations and value chains in the agri-food sector, organic farming, food production safety issues, questions of food labelling, health claims, novel food, patents, the role of institutions such as EFSA, the responsibility of trade and CSR. Legal frameworks, essential concerns and future developments of food security, food safety and food quality are the basis for discussion and solution finding."--